A new species of the genus Discoelius Latreille, 1809 (Hymenoptera: Vespidae: Eumeninae) from India - Pannure, Arati; Belavadi, Vasuki V.; Carpenter, James M. (Zootaxa, 2017)
Discoelius vasukii Pannure & Carpenter, sp. nov. is described and illustrated from Tamil Nadu, India. Discoelius Latreille, 1809 is a small genus of solitary wasp with ten species and one subspecies described, of which D. aurantiacus Nguyen, D. emeishanensus Zhou & Li, D. esakii Yasumatsu, D. longinodus Yamane, D. nigriclypeus Zhou & Li, D. turneri (Meade-Waldo), D. wangi Yamane and D. zonalis (Panzer) are recorded from Oriental Region (Zhou et al. 2013; Nguyen 2016). Only a single species, D. turneri described from Shillong (Meghalaya) (Meade-Waldo, 1910) and later recorded from Sikkim (Giordani Soika 1960) has been previously known from India. In this study, we describe a new species of Discoelius from India based on a single female specimen collected at Valparai (Tamil Nadu), India.